VD_FINDINFO Jug / 2025 / 258 vom 5. November 2024 - VD Tribunal cantonal (2024)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, PEINE PÉCUNIAIRE, SURSIS À L'EXÉCUTION DE LA PEINE | 106 CP, 42 al. 1 CP, 44 al. 1 CP, 47 CP, 90 al. 2 LCR